Layered manganese-based material as well as preparation method and application thereof
By optimizing the preparation process of layered manganese-based materials, including low-temperature sintering, high-temperature sintering, ion exchange treatment and annealing, the problems of poor oxygen stability and structural migration phase transition of traditional layered manganese-based materials are solved, and a layered manganese-based material with high energy density and good cycle stability is achieved, which is suitable for commercial applications of lithium-ion batteries.
Patent Information
- Application Number
- CN202510097115.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional layered manganese-based cathode materials have problems of poor oxygen stability and structural migration phase transition during recycling, resulting in rapid attenuation of capacity and voltage, limiting their practical application and commercialization prospects.
By mixing manganese, sodium and lithium sources, and then performing low-temperature sintering, high-temperature sintering, ion exchange treatment and annealing in turn, the preparation process of layered manganese-based materials is optimized, and the temperature control procedure of sintering is controlled to improve the stability and specific capacity of the material.
It significantly improves the discharge specific capacity and cycle stability of layered manganese-based materials, solves the problem of insufficient stability, is suitable for the commercial application of lithium-ion batteries, and helps promote the development of energy storage of clean energy.
Smart Images

Figure CN119706949A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery materials, and in particular relates to a layered manganese-based material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have become the main choice in the field of energy storage and power batteries due to their superior energy density and wide applicability. However, the overall performance and cost of lithium-ion batteries are largely subject to the selection and optimization of cathode materials.
[0003] At present, cobalt-based and nickel-based lithium-ion battery cathode materials are widely used due to their good electrochemical properties, but these materials have limited resources, high costs and negative impacts on the environment. In contrast, layered manganese-based cathode materials have gradually become an important candidate for the next generation of cathode materials due to their advantages such as abundant resources, low prices and high energy density. However, traditional layered manganese-based cathode materials have problems with poor oxygen stability and structural migration phase change during cyclic use. These problems lead to rapid attenuation of capacity and voltage, and ultimately lead to poor cycle stability and low specific capacity of layered manganese-based cathode materials, which seriously limit their practical application and commercial prospects. Summary of the invention
[0004] The purpose of the present invention is to provide a layered manganese-based material and a preparation method and application thereof. The layered manganese-based material provided by the present invention has a high energy density (high specific capacity) and good cycle stability, is suitable for the commercial application of lithium-ion batteries, and helps to promote the development of clean energy storage.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a layered manganese-based material, comprising the following steps:
[0007] Mixing a manganese source, a sodium source and a lithium source to obtain a mixed material;
[0008] The mixed material is sintered to obtain a precursor material; the sintering includes sequentially performing low-temperature sintering and high-temperature sintering; the insulation temperature of the low-temperature sintering is 400-600° C., and the insulation temperature of the high-temperature sintering is 600-900° C.;
[0009] The precursor material is mixed with a molten salt to perform an ion exchange treatment to obtain a treated material; the molten salt is a molten lithium salt;
[0010] The treated material is annealed to obtain the layered manganese-based material.
[0011] Preferably, the manganese source includes one or more of MnCl2, MnCO3, MnNO3 and (CH3COO)2Mn;
[0012] The sodium source includes one or more of NaCl, Na2CO3, NaNO3 and CH3COONa;
[0013] The lithium source includes one or more of LiCl, Li2CO3, LiNO3 and CH3COOLi;
[0014] The molar ratio of the manganese source to the sodium source is 0.5-0.8:0.1-0.3; the molar ratio of the manganese source to the lithium source is 0.5-0.8:0.1-0.3.
[0015] Preferably, the holding time of the low-temperature sintering is 5 to 10 hours; the holding time of the high-temperature sintering is 10 to 30 hours; the heating rate from room temperature to the holding temperature of the low-temperature sintering and the heating rate from the holding temperature of the low-temperature sintering to the holding temperature of the high-temperature sintering are independently 1 to 5°C / min.
[0016] Preferably, the molten salt is one or more of LiNO3, LiCl, Li2CO3 and CH3COOLi;
[0017] The mass ratio of the precursor material to the molten salt is 1:1 to 20;
[0018] The time of the ion exchange treatment is 5 to 10 hours.
[0019] Preferably, the annealing holding temperature is 200-400° C., and the holding time is 5-8 hours; the heating rate from room temperature to the annealing holding temperature is 1-5° C. / min.
[0020] The present invention provides a layered manganese-based material prepared by the preparation method described in the above technical solution.
[0021] The present invention provides the use of the layered manganese-based material described in the above technical solution as a positive electrode material in an energy storage device or a power battery.
[0022] The present invention provides a positive electrode material, wherein the active component of the positive electrode material is the layered manganese-based material described in the above technical solution.
[0023] The present invention provides a battery positive electrode, comprising a current collector and a positive electrode material arranged on the surface of the current collector, wherein the positive electrode material is the positive electrode material described in the above technical solution.
[0024] The present invention provides a battery, wherein the positive electrode of the battery is the positive electrode of the battery described in the above technical solution.
[0025] The present invention provides a method for preparing a layered manganese-based material, comprising the following steps: mixing a manganese source, a sodium source and a lithium source to obtain a mixed material; sintering the mixed material to obtain a precursor material; the sintering includes sequentially performing low-temperature sintering and high-temperature sintering; the insulation temperature of the low-temperature sintering is 400-600°C, and the insulation temperature of the high-temperature sintering is 600-900°C; mixing the precursor material with a molten salt for ion exchange treatment to obtain a treated material; the molten salt is a molten lithium salt; annealing the treated material to obtain the layered full manganese-based material. The preparation method provided by the present invention optimizes the preparation process of the layered manganese-based material, sequentially performs sintering, ion exchange treatment and annealing, and simultaneously controls the temperature control program of sintering: sequentially performing low-temperature sintering and high-temperature sintering; simultaneously controlling the insulation temperature of the low-temperature sintering to be 400-600°C, and the insulation temperature of the high-temperature sintering to be 600-900°C; not only significantly improves the discharge specific capacity of the layered manganese-based material, but also solves the problem of insufficient stability of the layered manganese-based material. Therefore, the layered manganese-based material prepared by the present invention has high energy density and good cycle stability, is suitable for the commercial application of lithium-ion batteries, and helps promote the development of clean energy storage.
[0026] At the same time, the layered manganese-based material prepared by the present invention does not introduce other transition metal ions, and the obtained is a full manganese-based positive electrode material (LMO). Therefore, on the basis of improving the specific capacity and cycle stability of the layered manganese-based material, the low cost advantage of the layered manganese-based material is maintained, and it is very suitable for the commercial application of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A flow chart for preparing the layered manganese-based material provided by the present invention;
[0028] Figure 2 The figure is a rate performance curve diagram of the button batteries prepared in Example 1 and Comparative Example 1;
[0029] Figure 3 The cycle performance curves of the button batteries prepared in Example 1 and Comparative Example 1 at a current density of 0.1C;
[0030] Figure 4 The cycle performance curves of the button batteries prepared in Example 1 and Comparative Example 1 at a current density of 0.5C;
[0031] Figure 5 This is a scanning electron microscope image of the layered manganese-based material prepared in Comparative Example 1;
[0032] Figure 6 This is a scanning electron microscope image of the layered manganese-based material prepared in Example 1. DETAILED DESCRIPTION
[0033] The present invention provides a method for preparing a layered manganese-based material, comprising the following steps:
[0034] Mixing a manganese source, a sodium source and a lithium source to obtain a mixed material;
[0035] The mixed material is sintered to obtain a precursor material; the sintering includes sequentially performing low-temperature sintering and high-temperature sintering; the insulation temperature of the low-temperature sintering is 400-600° C., and the insulation temperature of the high-temperature sintering is 600-900° C.;
[0036] The precursor material is mixed with a molten salt to perform an ion exchange treatment to obtain a treated material; the molten salt is a molten lithium salt;
[0037] The treated material is annealed to obtain the layered manganese-based material.
[0038] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0039] The present invention mixes a manganese source, a sodium source and a lithium source to obtain a mixed material. In the present invention, the manganese source preferably includes one or more of MnCl2, MnCO3, MnNO3 and (CH3COO)2Mn. The sodium source preferably includes one or more of NaCl, Na2CO3, NaNO3 and CH3COONa. The lithium source preferably includes one or more of LiCl, Li2CO3, LiNO3 and CH3COOLi. The molar ratio of the manganese source to the sodium source is preferably 0.5-0.8:0.1-0.3, more preferably 0.6-0.7:0.15-0.25, and in the embodiment it can be 0.7:0.25 or 0.8:0.3. The molar ratio of the manganese source to the lithium source is preferably 0.5-0.8:0.1-0.3, more preferably 0.6-0.7:0.15-0.25, and in the embodiment it can be 0.7:0.19 or 0.8:0.3. In the present invention, the specific implementation of the mixing is preferably grinding. The present invention has no special requirements for the specific implementation of the grinding, as long as the manganese source, sodium source and lithium source are mixed evenly. In the present invention, the preparation ratio of the manganese source, sodium source and lithium source is limited to the above range, which can optimize the capacity performance and cycle stability of the layered manganese-based material, and obtain a layered manganese-based material with higher specific capacity and better cycle stability.
[0040] After obtaining the mixed material, the present invention sintered the mixed material to obtain a precursor material. In the present invention, the sintering is preferably carried out in a heating furnace. The present invention preferably loads the mixed material into a porcelain boat and then puts it into the heating furnace for sintering. In the present invention, the sintering atmosphere preferably includes one or more of air, oxygen and argon. The sintering includes low-temperature sintering and high-temperature sintering in sequence. The insulation temperature of the low-temperature sintering is 400-600°C, preferably 450-550°C, and can be 500°C or 600°C in the embodiment; the insulation time is preferably 5-10h, more preferably 6-8h, and can be 6h or 10h in the embodiment. The heating rate from room temperature to the insulation temperature of the low-temperature sintering is preferably 1-5°C / min, more preferably 3-5°C / min. The holding temperature of the high temperature sintering is 600-900°C, preferably 600-800°C, and can be 650°C or 900°C in the embodiment; the holding time is preferably 10-30h, more preferably 15-24h, and can be 20h or 30h in the embodiment. The heating rate from the holding temperature of the low temperature sintering to the holding temperature of the high temperature sintering is preferably 1-5°C / min, more preferably 3-5°C / min. In the present invention, by controlling the sintering parameters within the above range, the layered manganese-based material with higher specific capacity and better cycle stability can be obtained.
[0041] During the sintering process, the larger diameter Na + It can temporarily stabilize the layered structure of the material. At the same time, during the sintering process, sodium ions can effectively avoid Mn 3+ The disproportionation reaction (2Mn 3+ →Mn 4+ +Mn +2 ), thereby preventing the material from collapsing into a spinel or disordered structure and improving the stability of the layered structure.
[0042] At the same time, sodium ions provide spatial isolation for the manganese ion layer, limiting the disordered migration of manganese ions between layers and preventing manganese ions from migrating from the layered structure to the octahedral sites or forming a spinel structure.
[0043] After obtaining the precursor material, the present invention mixes the precursor material with a molten salt for ion exchange treatment to obtain a treated material; the molten salt is a molten lithium salt. In the present invention, the molten salt is preferably one or more of LiNO3, LiCl, Li2CO3 and CH3COOLi, more preferably at least two of LiNO3, LiCl, Li2CO3 and CH3COOLi, and in the embodiment it can be LiNO3 and LiCl, and the mass ratio of LiNO3 and LiCl is preferably 8 to 9:1 to 2, and in the embodiment it can be 8.8:1.2. The mass ratio of the precursor material and the molten salt is preferably 1:1 to 20, more preferably 1:5 to 15, and in the embodiment it can be 1:10 or 1:20. In the present invention, the ion exchange treatment is preferably carried out under grinding conditions, and the time of the ion exchange treatment is preferably 5 to 10 hours, preferably 5 to 8 hours. The present invention mixes the precursor material with a molten salt, and uses a molten salt method to perform ion exchange treatment on the precursor material.
[0044] The present invention replaces sodium ions with lithium ions through ion exchange, thereby reducing local defects in the material and improving electrochemical performance.
[0045] The present invention exchanges the Na ions in the precursor material into Li ions to obtain the structure of the layered manganese-based material. During the above-mentioned high-temperature sintering process, the manganese ions easily migrate into the lithium layer, causing cation mixing and reducing the electrochemical properties of the material. The present invention can suppress the disordered migration of manganese ions between layers during the sintering process by adding a sodium source raw material, thereby suppressing cation mixing. Then, by ion exchange, a lithium ion material (layered lithium manganate) is obtained.
[0046] After obtaining the treated material, the present invention anneals the treated material to obtain the layered manganese-based material. In the present invention, the annealing is preferably carried out in a heating furnace. The present invention preferably loads the treated material into a porcelain boat and then puts it into the heating furnace for annealing. In the present invention, the annealing atmosphere preferably includes one or more of air, oxygen and argon. The annealing holding temperature is preferably 200-400°C, more preferably 250-350°C, and can be 280°C or 400°C in the embodiment; the holding time is preferably 5-8h, more preferably 6-7h, and can be 6h or 8h in the embodiment. The heating rate from room temperature to the annealing holding temperature is preferably 1-5°C / min, more preferably 3-5°C / min. The present invention can effectively improve the oxygen stability of the layered manganese-based material through annealing treatment, while inhibiting the structural migration phase change, thereby improving the cycle performance of the layered manganese-based material.
[0047] In the present invention, the annealed material is obtained after the annealing. The present invention preferably sequentially washes and dries the annealed material to obtain the layered manganese-based material. The washing is preferably performed with deionized water. The washing is preferably performed until the annealed material is neutral. The present invention has no special requirements for the specific implementation of the drying.
[0048] The present invention provides a layered manganese-based material prepared by the preparation method described in the above technical solution. The layered manganese-based material provided by the present invention is a full manganese-based material (the full manganese-based material prepared in the embodiment is specifically Li 0.9 Mn 0.83 O2), without doping with other transition metal elements. The layered manganese-based material provided by the present invention is a low-cost and high-capacity manganese-based positive electrode material. Compared with traditional lithium battery positive electrode materials (such as lithium cobalt oxide, NMC ternary), the layered manganese-based material provided by the present invention has the advantages of lower cost, higher energy density and environmental friendliness. The layered manganese-based material provided by the present invention has the advantages of low cost and high specific capacity, is suitable for the commercial application of lithium-ion batteries, and promotes the practical promotion of manganese-based positive electrode materials.
[0049] The present invention provides the use of the layered manganese-based material described in the above technical solution as a positive electrode material in an energy storage device or a power battery. In the present invention, the power battery is preferably an ion battery, specifically a lithium ion battery.
[0050] The present invention provides a positive electrode material, wherein the active ingredient of the positive electrode material is the layered manganese-based material described in the above technical solution. In the present invention, the positive electrode material preferably includes an active ingredient, conductive carbon black (SP) and a binder. In the present invention, the binder is preferably polyvinylidene fluoride (PVDF). The mass ratio of the active ingredient, conductive carbon black and binder is preferably 8:1:1.
[0051] The present invention provides a positive electrode for a battery, comprising a current collector and a positive electrode material disposed on the surface of the current collector, wherein the positive electrode material is the positive electrode material described in the above technical solution. In the present invention, the method for preparing the positive electrode for the battery preferably comprises the following steps: mixing the positive electrode material and an organic solvent to obtain a positive electrode material slurry; coating the positive electrode material slurry on the surface of the current collector, and then removing the solvent to obtain the positive electrode material. In the present invention, the current collector is preferably aluminum foil. The organic solvent is preferably N-methylpyrrolidone (NMP). The present invention has no special requirements for the amount of the organic solvent, as long as the coating is smoothly carried out.
[0052] The present invention provides a battery, wherein the positive electrode of the battery is the positive electrode of the battery described in the above technical solution. In the present invention, the battery is preferably a lithium ion battery, and the counter electrode of the lithium ion battery is preferably a metal lithium sheet. The electrolyte of the lithium ion battery is preferably a LiPF6 solution, and the molar concentration of LiPF6 in the LiPF6 solution is preferably 1M. The LiPF6 solution preferably includes LiPF6, an organic solvent and an additive, and the additive is preferably fluoroethylene carbonate (FEC). The mass percentage of the additive in the LiPF6 solution is preferably 5%. The organic solvent in the LiPF6 solution preferably includes ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC). The volume ratio of EC, DMC and EMC is preferably 1:1:1.
[0053] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0054] The preparation flow chart of the layered manganese-based material provided in the following examples is as follows Figure 1 shown.
[0055] Example 1
[0056] Fully grinding and mixing a manganese source (MnCO3), a sodium source (Na2CO3) and a lithium source (Li2CO3) in a mortar, wherein the molar ratio of MnCO3, Na2CO3 and Li2CO3 is 0.7:0.25:0.19; obtaining a mixed material;
[0057] The mixed material is loaded into a porcelain boat, heated to 500°C in a heating furnace at a heating rate of 5°C / min, maintained at a constant temperature for 6 hours, and then continued to be heated to 650°C at a rate of 5°C / min, maintained at a constant temperature for 20 hours. The atmosphere filled in the heating furnace is air, and a precursor material is obtained.
[0058] The precursor material and molten lithium salt (LiNO3 and LiCl) are fully ground in a mortar for ion exchange treatment, and the grinding is fully carried out for 10 minutes, wherein the mass ratio of the precursor material to the molten lithium salt is 1:10, wherein the molten lithium salt is LiNO3 and LiCl, and the mass ratio of LiNO3 to LiCl is 8.8:1.2; and a treated material is obtained;
[0059] The treated material was loaded into a porcelain boat, heated to 280°C in a heating furnace at a heating rate of 5°C / min, and kept at a constant temperature for 6 hours. The atmosphere filled in the heating furnace was air, and an annealed treated material was obtained.
[0060] The annealed material was washed with deionized water until neutral, filtered and dried thoroughly to obtain a layered manganese-based material. The layered manganese-based material (full manganese-based material, chemically Li 0.9 Mn 0.83 The scanning electron microscope image of O2) is as follows Figure 6 As shown by Figure 6 It can be seen that the product prepared in this embodiment is a layered structure product.
[0061] Comparative Example 1
[0062] Fully grinding and mixing a manganese source (MnCO3), a sodium source (Na2CO3) and a lithium source (Li2CO3) in a mortar, wherein the molar ratio of MnCO3, Na2CO3 and Li2CO3 is 0.7:0.25:0.19; obtaining a mixed material;
[0063] The mixed material was placed in a porcelain boat, heated to 650° C. at a heating rate of 5° C. / min in a heating furnace, and kept at a constant temperature for 20 hours. The atmosphere filled in the heating furnace was air, and a precursor material was obtained.
[0064] The precursor material and molten salt (LiNO3 and LiCl) were fully ground in a mortar for ion exchange treatment, and the grinding was fully performed for 10 minutes, wherein the mass ratio of the precursor material, LiNO3 and LiCl was 1:8.8:1.2; and a treated material was obtained;
[0065] The treated material was loaded into a porcelain boat, heated to 280°C in a heating furnace at a heating rate of 5°C / min, and kept at a constant temperature for 6 hours. The atmosphere filled in the heating furnace was air, and an annealed treated material was obtained.
[0066] The annealed material was washed with deionized water until neutral, filtered and dried thoroughly to obtain a manganese-based material. Figure 5 As shown by Figure 5 It can be seen that the product prepared in this comparative example is a layered structure product.
[0067] Test Case
[0068] The electrochemical performance of the positive electrode materials prepared in Example 1 and Comparative Example 1 was tested.
[0069] In the process of making the positive electrode sheet, firstly, the active material (the layered manganese-based material prepared in Example 1 or Comparative Example 1), SP and NMP organic solution containing PVDF need to be mixed in a mass ratio of active material: SP: PVDF = 8:1:1.
[0070] When mixing, ensure that the components are evenly distributed to form a slurry with a certain viscosity.
[0071] This mixed slurry was then evenly coated on the aluminum foil using a doctor blade.
[0072] After coating, the aluminum foil was placed in a vacuum drying oven at 80° C. and dried for 8 hours to remove moisture.
[0073] Subsequently, it was transferred to a vacuum drying oven at 110° C. and dried again for 6 hours to fully remove the organic solvent.
[0074] When assembling button cells, the operation is usually carried out in a protective atmosphere glove box filled with argon.
[0075] A metallic lithium sheet was used as the counter electrode, and the electrolyte was prepared by dissolving 1 M LiPF8 in an organic solvent mixed with EC, DMC and EMC in a volume ratio of 1:1:1, and FEC accounting for 5% of the volume percentage of the electrolyte was added as an additive.
[0076] The separator model used is Celgard 2320, which ensures good isolation of the battery and avoids short circuit.
[0077] During assembly, the negative electrode shell, spring sheet, gasket, lithium sheet, diaphragm, electrolyte, positive electrode sheet and positive electrode shell are assembled in order from bottom to top.
[0078] Finally, seal the assembled battery to ensure the battery's sealing.
[0079] The button batteries prepared from the materials of Example 1 and Comparative Example 1 were subjected to rate test curves at 0.1C, 0.2C, 0.5C, 1C, 2C and 5C. The performance is shown in the following figure. Figure 2 shown.
[0080] The button cells prepared from the materials of Example 1 and Comparative Example 1 were subjected to a 0.1C long cycle test curve, and the performance was as follows: Figure 3 shown.
[0081] The button cells prepared from the materials of Example 1 and Comparative Example 1 were subjected to a 0.5C long cycle test curve, and the performance was as follows: Figure 4 shown.
[0082] Depend on Figure 2 , Figure 3 and Figure 4 It can be seen that in the sintering process of Comparative Example 1, only high-temperature sintering (600-900° C.) is performed, and the discharge specific capacity and cycle stability of the obtained manganese-based material are significantly inferior to those of the product prepared in the example.
[0083] Example 2
[0084] The preparation method is basically the same as that of Example 1, except that the molar ratio of MnCl2, NaCl and LiCl is 0.8:0.3:0.3.
[0085] Example 3
[0086] The preparation method is basically the same as that of Example 1, except that the mass ratio of the precursor material to the molten lithium salt is 1:20, wherein the molten lithium salt is LiNO3 and LiCl, and the mass ratio of LiNO3 to LiCl is 17.6:2.4.
[0087] Example 4
[0088] The preparation method is basically the same as that of Example 1, except that the mixed material is loaded into a porcelain boat, heated to 600°C in a heating furnace at a heating rate of 5°C / min, maintained at a constant temperature for 10 hours, and then continued to be heated to 900°C at a rate of 5°C / min, maintained at a constant temperature for 30 hours, and the atmosphere filled in the heating furnace is air to obtain a precursor material.
[0089] Example 5
[0090] The preparation method is basically the same as that of Example 1, except that the treated material is loaded into a porcelain boat, heated to 400°C in a heating furnace at a heating rate of 5°C / min, and maintained at a constant temperature for 8 hours. The atmosphere filled in the heating furnace is air, and an annealed treated material is obtained.
[0091] The test performance results of the lithium-ion batteries prepared from the layered manganese-based materials prepared in Examples 2 to 5 are similar to those in Example 1.
[0092] As can be seen from the above embodiments, the present invention obtains a mixture of a manganese source, a sodium source and a lithium source in a certain proportion, and then sequentially sintering, ion-exchanging and annealing the mixture, thereby significantly improving the discharge specific capacity and cycle performance of the material, and does not introduce other transition metal ions, thereby maintaining the characteristics of low cost and high specific capacity. The manganese-based positive electrode material prepared by the present invention has a high energy density and good cycle stability, is suitable for the commercial application of lithium-ion batteries, and helps promote the development of clean energy storage.
[0093] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a layered manganese-based material, characterized in that: The following steps are involved: Mixing a manganese source, a sodium source and a lithium source to obtain a mixed material; The mixed material is sintered to obtain a precursor material; the sintering includes sequentially performing low-temperature sintering and high-temperature sintering; the insulation temperature of the low-temperature sintering is 400-600° C., and the insulation temperature of the high-temperature sintering is 600-900° C.; The precursor material is mixed with a molten salt to perform an ion exchange treatment to obtain a treated material; the molten salt is a molten lithium salt; The treated material is annealed to obtain the layered manganese-based material.
2. The preparation method according to claim 1, characterized in that: The manganese source includes one or more of MnCl2, MnCO3, MnNO3 and (CH3COO)2Mn; The sodium source includes one or more of NaCl, Na2CO3, NaNO3 and CH3COONa; The lithium source includes one or more of LiCl, Li2CO3, LiNO3 and CH3COOLi; The molar ratio of the manganese source to the sodium source is 0.5-0.8:0.1-0.3; the molar ratio of the manganese source to the lithium source is 0.5-0.8:0.1-0.
3.
3. The preparation method according to claim 1, characterized in that: The holding time of the low-temperature sintering is 5 to 10 hours; the holding time of the high-temperature sintering is 10 to 30 hours; the heating rate from room temperature to the holding temperature of the low-temperature sintering and the heating rate from the holding temperature of the low-temperature sintering to the holding temperature of the high-temperature sintering are independently 1 to 5°C / min.
4. The preparation method according to claim 1, characterized in that: The molten salt is one or more of LiNO3, LiCl, Li2CO3 and CH3COOLi; The mass ratio of the precursor material to the molten salt is 1:1 to 20; The time of the ion exchange treatment is 5 to 10 hours.
5. The preparation method according to claim 1, characterized in that: The annealing holding temperature is 200-400° C., and the holding time is 5-8 hours; the heating rate from room temperature to the annealing holding temperature is 1-5° C. / min.
6. The layered manganese-based material prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the layered manganese-based material according to claim 6 as a positive electrode material in an energy storage device or a power battery.
8. A positive electrode material, characterized in that The active ingredient of the positive electrode material is the layered manganese-based material according to claim 6.
9. A positive electrode of a battery, characterized in that: It comprises a current collector and a positive electrode material arranged on the surface of the current collector, and the positive electrode material is the positive electrode material according to claim 8.
10. A battery, characterized in that: The positive electrode of the battery is the positive electrode of the battery according to claim 9.
Citation Information
Patent Citations
Lithium-rich manganese-based cathode material and preparation method thereof, positive electrode piece and lithium ion secondary battery
CN110010886A
Total-manganese or high-manganese-based lithium-rich layered cathode material with disordered intra-layer cations and preparation method thereof
CN112299487A
Energy storage equipment, lithium manganese oxide and preparation method and application thereof
CN113912128A
High-capacity lithiated manganese-based layered oxide positive electrode material as well as preparation method and application thereof
CN114229909A
Layered cobalt-free manganese-based lithium ion battery positive electrode material as well as preparation method and application thereof
CN114242969A
Cited By
Single-crystal positive electrode material for sodium-ion battery and preparation method and application of single-crystal positive electrode material
CN121123256A